1996
DOI: 10.1105/tpc.8.11.2067
|View full text |Cite
|
Sign up to set email alerts
|

An octadecanoid pathway mutant (JL5) of tomato is compromised in signaling for defense against insect attack.

Abstract: The activation of defense genes in tomato plants has been shown to be mediated by an octadecanoic acid-based signaling pathway in response to herbivore attack or other mechanical wounding. We report here that a tomato mutant (JL5) deficient in the activation of wound-inducible defense genes is also compromised in resistance toward the lepidopteran predator Manduca sexta (tobacco hornworm). Thus, we propose the name defenselessí (defl) for the mutation in the JL5 line that mediates this altered defense response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
165
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(175 citation statements)
references
References 46 publications
5
165
2
3
Order By: Relevance
“…Methyl jasmonate (JA-Me) has also been found to induce gum in tulip bulbs and stems (Saniewski 1989, Saniewski and Puchalski 1988, Saniewski et al 1997. Recent studies demonstrated an important role of JA and its related compounds in the signal transduction pathway in response to stresses such as wounding, insect attack, or pathogen infection (Blechert et al 1995, Howe et al 1996, Mueller 1997, Reinbothe et al 1994, Sembdner and Parthier 1993, Seo et al 1997. These facts suggest that gummosis in trees in response to these stresses is regulated by JA and its related compounds in a way similar to the mode of action of ethylene.…”
mentioning
confidence: 77%
“…Methyl jasmonate (JA-Me) has also been found to induce gum in tulip bulbs and stems (Saniewski 1989, Saniewski and Puchalski 1988, Saniewski et al 1997. Recent studies demonstrated an important role of JA and its related compounds in the signal transduction pathway in response to stresses such as wounding, insect attack, or pathogen infection (Blechert et al 1995, Howe et al 1996, Mueller 1997, Reinbothe et al 1994, Sembdner and Parthier 1993, Seo et al 1997. These facts suggest that gummosis in trees in response to these stresses is regulated by JA and its related compounds in a way similar to the mode of action of ethylene.…”
mentioning
confidence: 77%
“…Wounding was achieved by crushing the lower leaf perpendicular to the midvein using a hemostat. Systemin was supplied to excised plants through their cut stems at a concentration of 28 nM as described in Howe et al (1996). Plants were exposed to methyl jasmonate vapors as previously described (Bergey and Ryan 1999).…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…After leaf wounding, JA concentrations in wounded leaves increase rapidly and transiently, with pools waxing and waning within minutes Blechert et al 1995;Baldwin et al 1997;Creelman and Mullet 1997). This JA burst precedes the activation of several defense-related genes (Creelman et al 1992;Doares et al 1995b) and the accumulation of plant defense compounds, including proteins (Doares et al 1995b;Howe et al 1996), alkaloids (Dittrich and Kutchan 1991;Baldwin et al , 1997Baldwin 1996), avonoids (Gundlach et al 1992Mueller et al 1993), and phenolics (Mizukami et al 1993). In comparison, SA displays a slower, more attenuated response to tobacco mosaic virus (TMV) inoculation, with systemic increases occurring several days after inoculation and lasting for several weeks (Raskin 1992).…”
Section: Introductionmentioning
confidence: 97%